P219 Does a specialised MSM clinic in a district general hospital attract a riskier population?. (18th May 2015) - Oduru, Mamatha; Wainwright, Emma; Burnett, Janice; Tang, Alan
Abstract : Background/introduction: A sexual health service for men who have sex with men (MSM) was piloted due to local demand for a specialised clinic with an understanding of MSM risk taking behaviour and sexual practices. Aim(s)/objectives: To explore if an MSM clinic in a district general hospital attracts a patient population with riskier sexual behaviour compared to the normal genitourinary (GU) service. Methods: Risk data was collected from all MSM patients attending the specialised and routine GU clinics over a 3 month period using self-completed questionnaires. 'High risk' behaviour was classified as any of the following within the past 3 months: group sex, sex parties, chem-sex, casual partner sourcing online, sexual activity in London and number of partners. Data were analysed in SPSS version 22. Results: Total sample size was 40 (MSM clinic, N = 13, GU clinic, N = 27). Age range was 18 to 67 years old (mean 32.47, standard deviation 11.48). Patients from both groups were involved in all behaviours, however MSM clinic patients were more likely to engage in risky sexual activity in London (p = 0.021) and source casual partners online (p = 0.029) compared to the GU clinic population. Discussion/conclusion: The MSM clinic attracted a population with riskier sexual behaviours. Patients cited non-judgemental acceptance and understanding of MSM sexual practices as pivotal for attending. Perceived reduction in stigma, rapid HIV testing and tailored advice has encouraged service engagement; this provides a valuable opportunity to screen and vaccinate patients at high risk of sexually transmitted infections.